Optical Fiber Communication Conference/National Fiber Optic Engineers Conference 2011 2011
DOI: 10.1364/ofc.2011.otuh2
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Optical Data Center

Abstract: Abstract:We review the architecture of modern datacenter networks, as well as their scaling challenges; then present high-level requirements for deploying optical technologies in datacenters, particularly focusing on optical circuit switching and WDM transceivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(37 citation statements)
references
References 6 publications
(9 reference statements)
0
37
0
Order By: Relevance
“…PCIe switch (Gen 3) can achieve latency on the order of 150 ns while low latency Top-of-Rack IP switch and Infiniband switch can achieve 800 ns latency or less. As a result, silicon photonics and optical circuit switches (OCS) are likely to be the only options to enable composable memory beyond a rack [34][35][36]. Large caches can reduce the impact of remote access.…”
Section: Software Stackmentioning
confidence: 99%
“…PCIe switch (Gen 3) can achieve latency on the order of 150 ns while low latency Top-of-Rack IP switch and Infiniband switch can achieve 800 ns latency or less. As a result, silicon photonics and optical circuit switches (OCS) are likely to be the only options to enable composable memory beyond a rack [34][35][36]. Large caches can reduce the impact of remote access.…”
Section: Software Stackmentioning
confidence: 99%
“…However, according to empirical studies of DC traffic, it has been shown that 80% of the flows are mice flows (smaller than 10 KB in size) and 95% of the bytes transferred in a DC are in the top 10% of the elephant flows (flows with large amount of data) [9]- [11], [104]. Thus, full bisection bandwidth between more than a few pairs of servers at any instant is rarely required in a DCN [35], [39], [103], [105].…”
Section: Proposed Classification Of Dcn Architecturesmentioning
confidence: 99%
“…In this scenario, optical networks are used to provide high-speed, on-demand, high bandwidth inter-rack communication in DCNs [35], [39], [40], [103], [105], [106]. Existing hybrid wired DCNs (e.g., c-Through and Helios) employ Electrical Packet Switching (EPS) and Optical Circuit Switching (OCS) technologies, respectively, for supporting bursty and long duration large flows in DCNs [34], [35], [39], [40], [107].…”
Section: Proposed Classification Of Dcn Architecturesmentioning
confidence: 99%
“…Albeit great part of the traffic will continue to flow between end-users and such computer centers, an increasing fraction is flowing within the DPCs themselves [2,3]. This situation has triggered a worldwide investment to upgrade the existing facilities or building new ones in order to cope with the growing bandwidth demand that has been estimated to reach $35BN in 2012 [4].…”
Section: Introductionmentioning
confidence: 99%